Atomic Force Microscope for Large Size Sample: 2nd Report, 0.1 nm Resolution and 25 mm-area Scanning - KUNITOMO, Yuichi; MURAYAMA, Ken; MORIMOTO, Takafumi; HOSAKA, Sumio (Transactions of the Japan Society of Mechanical Engineers Series C, 2006)
We have developed a new AFM (Atomic force microscopy) for semiconductor device evaluation with high resolution of 0.1 nm and wide-area measuring function to 25 mm area using two scanning mechanisms, a piezoelectric XY scanner of 10 im stroke combined with an on-axis optical microscope and an ultra-flat XY stage of 200 mm stroke moving on a reference plane with a static pressure guide or a contact friction guide switched to non-pressure. We demonstrated three operations, high-resolution mode with the piezoelectric scanner on the friction guide condition, middle-area mode from 5μm to 1mm area with the static pressure guide and 25mm wide-area mode with the friction guide. Finally, an atomic step of 0.3 nm height, CMP (Chemical Mechanical Polishing) samples with 2-10 mm measurement area and the flatness accuracy of 30 nm/25 mm were measured in one AFM.